Estimation of body measurements of sheep by Digital Image Processing - A.R. Onal (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT For the determination of body measurements in sheep the classical measurement method is generally used. However, measurements taken using classical methods are generally difficult, time-consuming, and often yield questionable results. In this study, the possibilities of using Image Processing Methods for measuring the body dimensions of Turkgeldi sheep were investigated. For this purpose, the body measurements of Turkgeldi sheep were determined using Image Processing Technology. In the study, measurements of 11 four-year-old Turkgeldi sheep raised at Namik Kemal University Research and Application Farm were obtained using both the traditional measurement method and image processing methods, and then the two methods were compared. To obtain measurements using the Image Processing Method, a scale with a diameter of 12 centimeters, divided into different colors for each centimeter, was placed on the animals as a reference point. The correlation coefficients between the methods for body measurements were calculated as 0.92 (P<0.01) for withers height (WH), 0.84 (P<0.01) for back height (BH), 0.82 (P<0.01) for rump height (RH), 0.83 (P<0.01) for back rump height (BRH), 0.61 (P<0.05) for chest deep (CD), 0.93 (P<0.01) for trunk length (TL), and 0.94 (P<0.01) for overall body length (BL).